POPULASI DAN SAMPEL DALAM PENELITIAN KUALITATIF - Desi Chayani Wulan; Zamsiswaya (STKIP Subang, 2026)
This study aims to analyze the concepts of population and sampling within the perspective of qualitative research, as well as the relevant sampling techniques in the context of scientific inquiry. The method employed is library research with a descriptive-analytical approach, involving the examination of various literature sources such as books and scholarly journals. The findings indicate that in qualitative research, the concept of population is not explicitly utilized; instead, it is replaced by the notion of a social situation, which encompasses aspects of place, actors, and activities. Sampling is conducted purposively and develops progressively through an emergent sampling design as well as the snowball sampling technique. The sample size is not determined statistically, but rather based on the level of data saturation. Therefore, the primary focus of qualitative research lies in the depth of information rather than the number of samples. These findings affirm that flexibility in sampling determination is a fundamental characteristic of qualitative research.